An enhanced chaotic encryption method for fragile watermarking - Boujarian, Sima (2013)
These days internet is one of the most important part of human life and the most significant issue that is connected to this technology is keeping data secure. Many attackers try to obtain secret information for different reason so sometimes it is necessary to keep existence of data secret. Cryptography and watermarking can combine to each other to create a secure platform for sensitive information. In some model even after combining encryption and watermarking the hidden message can be detectable. In our proposed model two type of encryption methods which are Arnold Cat Map and RSA algorithm are combined with LSB watermarking to make hidden message secure. This method creates confusion and diffusion to keep existence of information secure. Results show that the proposed model increase security of hidden message with lower time of implementation algorithm.